2019
DOI: 10.1002/anie.201904680
|View full text |Cite
|
Sign up to set email alerts
|

Ag10Ti28‐Oxo Cluster Containing Single‐Atom Silver Sites: Atomic Structure and Synergistic Electronic Properties

Abstract: Supported single‐atom catalysts have been emerging as promising materials in a variety of energy catalysis applications. However, studying the role of metal–support interactions at the molecular level remains a major challenge, primarily due to the lack of precise atomic structures. In this work, by replacing the frequently used TiO2 support with its molecular analogue, titanium‐oxo cluster (TOC), we successfully produced a new kind of Ti‐O material doped with single silver sites. The as‐obtained Ag10Ti28 clus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 57 publications
1
37
0
Order By: Relevance
“…[13][14][15][16][17][18][19] More importantly,o rganoaluminium with highly tailorable shape,c omposition, and surface properties represents an excellent platform for significant atomistic understanding.H owever, the fast hydrolysis of aluminum salts/alkoxides usually results in the formation of ametal oxide/hydroxide.Inthis regard, it is important to slow down its hydrolysis process to promote crystallization and simultaneously enable condensation occurs.R ecently,w eh ave applied organic ligands to delay the hydrolysis process of Ti IV ions through coordination interactions (denoted as coordination delayed hydrolysis (CDH)). [20][21][22][23][24] Therefore,w eb elieve the strategy can be used to understand the hydrolysis and condensation of Al III precursors,w hich remained relatively unexplored before. Considering the similar hydrolysis process between Ti IV and Al III ions,i ti sp redictable that the CDH strategy may bring an ew blueprint for constructing atomically-precise Almolecular architectures.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19] More importantly,o rganoaluminium with highly tailorable shape,c omposition, and surface properties represents an excellent platform for significant atomistic understanding.H owever, the fast hydrolysis of aluminum salts/alkoxides usually results in the formation of ametal oxide/hydroxide.Inthis regard, it is important to slow down its hydrolysis process to promote crystallization and simultaneously enable condensation occurs.R ecently,w eh ave applied organic ligands to delay the hydrolysis process of Ti IV ions through coordination interactions (denoted as coordination delayed hydrolysis (CDH)). [20][21][22][23][24] Therefore,w eb elieve the strategy can be used to understand the hydrolysis and condensation of Al III precursors,w hich remained relatively unexplored before. Considering the similar hydrolysis process between Ti IV and Al III ions,i ti sp redictable that the CDH strategy may bring an ew blueprint for constructing atomically-precise Almolecular architectures.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, some limited NN PES MD simulations have appeared in the material and catalysis science. 41 The adsorption and activation of CO molecule on a transition metal surface is often a critical elementary step for the catalytic conversion of CO into the high added-value chemicals, such as Fischer-Tropsch reaction, [42][43][44] CO 2 reduction, [45][46][47] and coal to ethylene glycol, [48][49][50] etc. Given the fact that there exist many active sites on the surface, presumably with different binding affinity to the substrates, intermediates, as well as transition states, a proper description of the adsorbate adsorption and movement between different sites on surface is thus clearly important for a correct understanding of the catalytic process.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19] In addition, the molecular characteristics of metal-oxo clusters allow convenient chemical functionalizationt hrough metal doping and ligand decoration. [20][21][22][23][24][25][26] From as tructural pointo f view,t he constructiono fP bTiO 3 can be attributed to the introductiono fl ead ions into titaniumo xides. Therefore, if lead ions could be dopedi nto the structure of titanium-oxo clusters, the molecular structure of PbTiO 3 might be prepared.I n the past decades, considerable efforts have been devoted to this area or research and as eries of lead-doped polyoxo-titanium clusters (Pb-PTCs) have been reported by Jagner,H ubert-Pfalzgraf,S chubert, and others.…”
Section: Introductionmentioning
confidence: 99%